Growth and survival of Indian salmon Eleutheronema tetradactylum (Shaw, 1804) in Brackish water pond. - Abu Hena, Mustafa Kamal; Idris, Mohd Hanafi; Wong, Sing King; Kibria, M. M. (Academic Journals, 2011)
This study was conducted to assess the growth performance and survival rate of a commercially important finfish Eleutheronema tetradactylum in 100 m-2 of sandy clay brackish water earthen ponds. Wild 36.14 g of E. tetradactylum juveniles were stocked at 0.5 individuals m-2 and cultured for 45 days by feeding trash Muraenesox sp. (pike eel) at 12 h intervals. Average body weight of E. tetradactylum was found 75±5.6 g for treatment ponds and 65±3.57 g for control ponds at the end of experiment. Feed Conversion Ratio (FCR) was 2.3 with the survival rate of 70-80% at the end of the culture in the experimental culture ponds. The results of the present study suggest that the production of four finger thread fin could still be increased up to the marketable size if it is done for 5-6 months culture period by feeding trash fish.